Modern Trends and Technologies of the Pedagogical Process in Primary School (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article discusses modern trends in the development of primary education in Uzbekistan. Activities of representatives of the Jadidism movement in the development of primary education. Analysis of the content of primary education and modern requirements for it. The article uses scientific theories of a number of psychologists and educators.